Anorexia Nervosa and a Lost Emotional Self: A Psychological Formulation of the Development, Maintenance, and Treatment of Anorexia Nervosa - Oldershaw, Anna; Startup, Helen; Lavender, Tony (Frontiers in Psychology, 2019)
In this paper, we argue that Anorexia Nervosa (AN) can be explained as arising from a ‘lost sense of emotional self’. We begin by briefly reviewing evidence accumulated to date supporting the consensus that a complex range of genetic, biological, psychological, and socioenvironmental risk and maintenance factors contribute to the development and maintenance of AN. We consider how current interventions seek to tackle these factors in psychotherapy and potential limitations. We then propose our theory that many risk and maintenance factors may be unified by an underpinning explanation of emotional processing difficulties leading to a lost sense of ‘emotional self’. Further, we discuss how, once established, AN becomes ‘self-perpetuating’ and the ‘lost sense of emotional self’ relentlessly deepens. We outline these arguments in detail, drawing on empirical and neuroscientific data, before discussing the implications of this model for understanding AN and informing clinical intervention. We argue that experiential models of therapy (e.g. emotion-focused therapy; schema therapy) be employed to achieve emergence and integration of an ‘emotional self’ which can be flexibly and adaptively used to direct an individual’s needs and relationships. Furthermore, we assert that this should be a primary goal of therapy for adults with established AN.